Long Noncoding RNA (lncRNA) CTTN-IT1 Elevates Skeletal Muscle Satellite Cell Proliferation and Differentiation by Acting as ceRNA for YAP1 Through Absorbing miR-29a in Hu Sheep - Wu, Tianyi; Wang, Shanhe; Wang, Lihong; Zhang, Weibo; Chen, Weihao; Lv, Xiaoyang; Li, Yue; Hussain, Zahid; Sun, Wei (Frontiers in Genetics, 2020)
Characterizing the factors that regulate the growth and development of muscle is central to animal production. Skeletal muscle satellite cells (SMSCs) provide an important material for simulating the proliferation and differentiation of muscle cells. YAP1, which can promote muscle growth, is closely related to the proliferation of SMSCs in Hu sheep (Ovis aries). In addition, some miRNAs, such as miR-541-3p, miR-142-5p, and miR-29a, can play critical roles in muscle growth by specifically binding with their target mRNAs. Meanwhile, lncRNA can competitively bind these miRNAs and reduce the regulatory effect of miRNAs on their target genes and thus play critical roles themselves in muscle growth. However, the regulatory molecular mechanism of miRNA and lncRNA on SMSC proliferation through YAP1 remains unclear. Here, we characterized the regulatory network among YAP1 and its targeted miRNAs and lncRNAs in Hu sheep SMSCs. The potential ncRNAs that regulate YAP1 (miR-29a and CTTN-IT1) were predicted through multilevel bioinformatics analysis. Dual-luciferase assays, RT-qPCR, and western blots revealed that miR-29a can significantly reduce the mRNA and protein expression level by binding to a specific 3′-UTR of YAP1 (P<0.05), while CTTN-IT1 can restore the expression of YAP1 through competitive binding to miR-29a. Furthermore, the mRNA and protein expression levels of MyoG, MyoD, and MyHC showed that miR-29a can inhibit the expression of genes related to the differentiation of SMSCs, and CTTN-IT1 can increase the expression of these same genes. Thus, miR-29a may inhibit the differentiation of SMSCs and CTTN-IT1 can restore this inhibition. The EdU staining assay indicated that excessive miR-29a can significantly reduce the proliferation ability of SMSCs (P<0.05), while overexpression of CTTN-IT1 can significantly increase the proliferation of SMSCs (P<0.01). CTTN-IT1 is a novel lncRNA that is a competing endogenous RNA (ceRNA) of miR-29a and can promote SMSC proliferation and differentiation by restoring the expression of YAP1 when it is inhibited by miR-29a in Hu sheep. Overall, our findings construct a CTTN-IT1-miR-29a-YAP1 regulatory network that will help contribute new insight into improving the muscle development of Hu sheep.